Chitosan suitability to adhesion, neuronal differentiation and maturation of hiPSCs compared to Matrigel coated substrates - Sara Grasselli; Donatella Di Lisa; Pier Francesco Ferrari; Sergio Martinoia; Laura Pastorino (Carbohydrate Polymer Technologies and Applications)
Human induced pluripotent stem cells (hiPSCs) derived neurons are revolutionising the study of patient-specific conditions. Typically, hiPSCs are expanded and differentiated onto Matrigel. However, to obtain a functional network, early-stage neurons are transferred to laminin/polyornithine (PORN/LAM) coated substrates, undergoing great stress that may hinder the complete network development. Finding an adhesion factor that supports the differentiation and maturation of the neural networks of hiPSCs derived neurons is therefore crucial. The ability of chitosan (CHI) in supporting the adhesion and development of functional neuronal networks has already been demonstrated for iNeurons, indicating CHI as an alternative to PORN/LAM.In this study, we investigated the bioactivity of CHI by comparing its ability to support the early-stage differentiation of hiPSCs to that of Matrigel. To this aim, cell adhesion, survival and differentiation was monitored over 14 days of culture both on culture supports functionalized with Matrigel and CHI. Cell differentiation was investigated via immunocytochemistry and western blot analysis. Stemness markers and neuronal markers were used to confirm the gradual differentiation of cells. Moreover, the early-stage differentiation was carried out onto CHI coated micro-electrode arrays in co-culture with primary astrocytes followed by the complete maturation of the neuronal network as demonstrated by recorded spontaneous electrophysiological activity.